Review: facilitating the acquisition of ballistic motor skills - promoting proximal or distal system perturbations? - Stodden, D. F. (Journal of Human Movement Studies, 2006)
The acquisition of ballistic motor skills including striking, throwing and kicking is fundamental for participation in many Sports and games. Answering the question of how to most effectively promote skill acquisition in ballistic skills has not been methodically addressed, in part due to their inherent complex coordination patterns involving multiple segments. The purpose of this paper is to review the literature on ballistic skill acquisition, describe and explain different intervention strategies that have been used to promote skill acquisition and alter coordination patterns and discuss their relative effects and limitations. This review will allow us to understand better how we can effectively and efficiently promote the acquisition of ballistic motor skills.